2003
DOI: 10.1002/art.11389
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic proteins 2 and 6, expressed in arthritic synovium, are regulated by proinflammatory cytokines and differentially modulate fibroblast‐like synoviocyte apoptosis

Abstract: Objective. To examine the expression, regulation, and potential roles of bone morphogenetic proteins (BMPs) in arthritic synovium.Methods. Expression of BMPs in arthritic synovium from patients with rheumatoid arthritis (RA) or spondylarthropathy (SpA) and in noninflamed synovium from patients undergoing diagnostic or therapeutic arthroscopies was studied by reverse transcriptionpolymerase chain reaction (RT-PCR), Western blot, immunohistochemistry, and 2-color immunofluorescence. In vitro regulation of gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
110
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 85 publications
(62 reference statements)
9
110
0
Order By: Relevance
“…Our finding of higher molecular forms of BMPs in osteoclasts might reflect the presence of proteolytically uncleaved precursor forms of BMPs or bands generated from posttranslational modifications such as glycosylation (partial or complete), as seen in other studies reporting BMP protein expression Kochanowska et al 2002;Wordinger et al 2002;Lories et al 2003;Schwalbe et al 2003). Another reason might be insufficient reduction by dithiotheritol of BMP multimers, at a concentration of 1 mM, which is routinely used in denaturing SDS gels.…”
Section: Western Blot Analysessupporting
confidence: 55%
“…Our finding of higher molecular forms of BMPs in osteoclasts might reflect the presence of proteolytically uncleaved precursor forms of BMPs or bands generated from posttranslational modifications such as glycosylation (partial or complete), as seen in other studies reporting BMP protein expression Kochanowska et al 2002;Wordinger et al 2002;Lories et al 2003;Schwalbe et al 2003). Another reason might be insufficient reduction by dithiotheritol of BMP multimers, at a concentration of 1 mM, which is routinely used in denaturing SDS gels.…”
Section: Western Blot Analysessupporting
confidence: 55%
“…Cheng, et al 24 demonstrated a specific role for osteoblasts during mesenchymal stem cell differentiation. Further, work by Lories, et al 25 supported the hypothesis that BMP6 could be a potent regulator of bone and cartilage repair in arthritis. Based on these results, we postulate that BMP6 may be responsible for helping to regulate joint motion and alignment during the progression of RA.…”
Section: Discussionmentioning
confidence: 85%
“…Sequential cleavage at two distinct sites within the pro-domain by furin or furin-like proteases is required for the activation of the BMP-4 precursor (20,21). Furthermore, proBMP-2 and proBMP-6 have been detected in arthritic synovial tissue (22). Whereas these results suggest a function of the pro-peptides in modulation of BMP activities, no specific function of the pro-peptide of BMP-2 could be assigned as yet.…”
mentioning
confidence: 71%